Microbial metabolite deoxycholic acid promotes vasculogenic mimicry formation in intestinal carcinogenesis. Issue 2 (6th December 2021) - Song, Xueli; An, Yaping; Chen, Danfeng; Zhang, Wanru; Wu, Xuemei; Li, Chuqiao; Wang, Sinan; Dong, Wenxiao; Wang, Bangmao; Liu, Tianyu; Zhong, Weilong; Sun, Tao; et al.
Abstract: A high‐fat diet (HFD) leads to long‐term exposure to gut microbial metabolite secondary bile acids, such as deoxycholic acid (DCA), in the intestine, which is closely linked to colorectal cancer (CRC). Evidence reveals that vasculogenic mimicry (VM) is a critical event for the malignant transformation of cancer. Therefore, this study investigated the crucial roles of DCA in the regulation of VM and the progression of intestinal carcinogenesis. The effects of an HFD on VM formation and epithelial‐mesenchymal transition (EMT) in human CRC tissues were investigated. The fecal DCA level was detected in HFD‐treated Apc min/+ mice. Then the effects of DCA on VM formation, EMT, and vascular endothelial growth factor receptor 2 (VEGFR2) signaling were evaluated in vitro and in vivo. Here we demonstrated that compared with a normal diet, an HFD exacerbated VM formation and EMT in CRC patients. An HFD could alter the composition of the gut microbiota and significantly increase the fecal DCA level in Apc min/+ mice. More importantly, DCA promoted tumor cell proliferation, induced EMT, increased VM formation, and activated VEGFR2, which led to intestinal carcinogenesis. In addition, DCA enhanced the proliferation and migration of HCT‐116 cells, and induced EMT process and vitro tube formation. Furthermore, the silence of VEGFR2 reduced DCA‐induced EMT, VM formation, and migration. Collectively, our results indicated that microbial metabolite DCA promoted VM formation and EMT through VEGFR2 activation, which further exacerbated intestinal carcinogenesis. Abstract : Our results demonstrated that an HFD led to VM formation and dysregulation of BA metabolism, especially increased DCA, which promoted the occurrence and progression of intestinal tumors. More importantly, DCA drove EMT and VM formation by modulating VEGFR2 signaling. Encouragingly, VM formation provided a novel understanding of the complex carcinogenic mechanism of DCA.